MA’HAD AL-ZAYTUN: PERAN SYAYKH AL-ZAYTUN DALAM MENYEMAI BENIH BUDAYA TOLERANSI DAN PERDAMAIAN DALAM BINGKAI PESANTREN - nisa, Chairunnisa; Al-Hazini, Anzar; Anisman; Idris, Fahmi; Ngainnur Rohmah, Siti (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Islamic boarding schools have long been known as educational institutions that not only teach religious knowledge, but also play an important role in forming character and a culture of tolerance and peace among their students. This research aims to explore how the leader of the Ma'had Al-Zaytun Islamic boarding school influences the formation of the character of tolerance and peace. This research uses qualitative methods with an empirical normative approach. Secondary data sources used include the book Al-Zaytun Sumber Inspirasi (ASI), Al-Zaytun magazine, Syaykh Al-Zaytun's sermons, and the work of DR. Al-Ustadz (Hon. M.S.U.) A.S. Panji Gumilang, M.P. associated with a culture of tolerance and peace. They do this through direct learning, interactive dialogue, and social activities involving students from various social and religious backgrounds. The results of the research show that the construction of tolerance thought built by Islamic boarding school leaders is inclusive, believes in the existence of truth in other religious beliefs, and is based on tasamuh, namely a moderate style of understanding of Islam. The implementation of the concept of tolerance is reflected in the curriculum and policies of Islamic boarding schools which prioritize multiculturalism and pluralism education. This research provides new insights into the strategic role of Islamic boarding schools in developing a culture of tolerance and peace, which is very relevant in the current era of globalization. This research uses qualitative methods, data sources and research results. Keywords: Culture of Tolerance, Peace, Islamic Boarding School Leader, Ma’had Al-Zaytun.